“It made me feel like a shit parent”: an intersectional analysis of pandemic mothering - Thorpe, Holly; Barrett, Nikki; Nemani, Mihi Joy; O'Leary, Grace; Ahmad, Nida (Frontiers in Sociology, 2024)
The COVID-19 pandemic brought to the fore the everyday and exceptional challenges for mothers. Rarely, however, did research or social commentary acknowledge the multiplicities of motherhood during this prolonged period of risk, disruption, and uncertainty. This paper draws upon interviews with 24 mothers living in Aotearoa New Zealand during the pandemic, including women who were pregnant and gave birth during lockdowns, teenage mothers, single and low-income mothers, and working mothers. The sample was intentionally diverse, including Māori, Pacific, Asian and migrant mothers. Engaging an intersectional lens on motherhood and women's health, this paper builds upon and extends feminist research on mothers' experiences during the pandemic, highlighting the many different challenges facing mothers of diverse social, cultural, and economic positionalities and during various stages of motherhood. Across the sample, we reveal the significant emotional toll on mothers, particularly with the absence of critical social, medical and health support systems during lockdown periods and sustained social restrictions. Many of the women described how the pandemic affected their feelings about motherhood, prompting new reflections on their relationships with the home, family, work, and broader society. Despite some similarities, the pandemic experiences of Māori, Pacific, migrant and single mothers were further intensified by various forms of isolation, judgement, and discrimination. In this way, the pandemic shed light on the gendering of everyday maternal life, but also the need for more intersectional culturally and gender-responsive policies that acknowledge the multi-layered complexities of mothers' lives.